Validity of home blood pressure measurements manually registered by patients after an educational session provided by community pharmacists. Issue 4 (August 2015) - Sendra-Lillo, José; Martínez-Martínez, Fernando; García-Corpas, José Pedro; Marín Rivas, Fátima; Sabater-Hernández, Daniel
Abstract : When home blood pressure (HBP) measurements are taken, the readings can be registered manually by the patient and/or stored in the device's memory. The instructions provided by healthcare professionals would be particularly relevant to guarantee the reliability of manual blood pressure (BP) figures and enhance clinical decision making. The aim of this study is assess the agreement between HBP measurements manually registered by patients and those stored in the device's memory after an educational session provided by community pharmacists. Secondary data of the MEPAFAR and the Palmera studies have been used in this analysis. All the (treated hypertensive) patients attended an individual educational session in which they were instructed on how to use the measurement device and properly measure and manually register HBP. The same device and HBP monitoring protocol were used in both studies: 4 consecutive days (three morning measurements and three in the evening). HBP measurements were both manually registered by patients and stored in the device's memory. To evaluate the agreement between BP figures, Lin's correlation–concordance coefficient and κ coefficient were used for quantitative and qualitative agreement, respectively. One hundred and sixty-sixty patients were included in this analysis. The agreement between the average manual and the stored HBP was very good [systolic=0.99, 95% confidence interval (CI): 0.99–0.99; diastolic=0.99, 95% CI: 0.99–1.00]. 99.4% of patients were classified in the same category by both alternatives [ κ index=0.99 (95% CI: 0.98–1.00)]. In this sample of treated hypertensive patients, the agreement between manually registered and stored BP figures was very good. This high concordance may be explained by the pharmacist's intervention. Abstract : Supplemental Digital Content is available in the text.